2020
DOI: 10.1111/all.14304
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous sensitization in the development of food allergy: What is the evidence and how can this be prevented?

Abstract: There is increasing evidence regarding the importance of allergic sensitization through the skin. In this review, we provide an overview of the atopic march and immune mechanism underlying the sensitization and effector phase of food allergy. We present experimental models and human data that support the concept of epicutaneous sensitization and how this forms one half of the dual‐allergen exposure hypothesis. We discuss specific important elements in the skin (FLG and other skin barrier gene mutations, Langer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(197 citation statements)
references
References 179 publications
(355 reference statements)
7
181
1
8
Order By: Relevance
“…It has been suggested that maintaining normal skin barrier function is critical for the prevention and control of allergic diseases such as AD and food allergy (FA) (14,16,(60)(61)(62). It is also well known that FLG deficiency and increased TEWL are associated with skin barrier dysfunction and increased allergen sensitization (20,35,(63)(64)(65).…”
Section: Ahr Is Essential In Maintaining Normal Skin Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that maintaining normal skin barrier function is critical for the prevention and control of allergic diseases such as AD and food allergy (FA) (14,16,(60)(61)(62). It is also well known that FLG deficiency and increased TEWL are associated with skin barrier dysfunction and increased allergen sensitization (20,35,(63)(64)(65).…”
Section: Ahr Is Essential In Maintaining Normal Skin Barrier Functionmentioning
confidence: 99%
“…The epidermis, the outermost part of the skin, provides a physical and functional barrier to prevent invasions of allergens, pathogens, and air pollutants such as PM into the human body (13)(14)(15). Recently, it has been suggested that a disrupted skin barrier promotes epicutaneous sensitization (14,16). Epithelial barrier dysfunction induces type 2 immune responses and is considered an initial step in developing atopic dermatitis (AD) and the atopic march (14,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…These are also increased interest in sensitive and specific biomarkers for diagnosis and for evaluation of disease severity and prognosis with therapy. With the understanding of the natural progression of the atopic diseases, studies are now in progress to determine whether by preventing skin sensitization and atopic dermatitis, we can prevent the subsequent manifestation of other atopic diseases, such as food allergy 118 . Some of the basic cellular and humoral factors involved in Th2‐mediated allergic diseases are well understood and have led to the development of biologics and other novel therapeutics, which are in various stages of development.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…However, the demonstration of a positive correlation between environmental non-oral peanut protein exposure levels and development of peanut allergy suggests non-oral environmental exposure as a potential route of sensitization 66 . The observed natural history of the “allergic march”, whereby individuals presenting with atopic dermatitis (AD) in infancy or early childhood proceed to develop concomitant sensitization to food and aeroallergens in later childhood and adult life, has led to the evolving concept of contribution from the skin as a route of food sensitization 67 71 . An archetypal example is AD, a common inflammatory skin disease in childhood affecting nearly 20–30% of the population and is associated with skin barrier disruption linked with mutations in human skin barrier genes filaggrin ( FLG ), serine peptidase inhibitor Kazal type 5 ( SPINK5 ), corneodesmosin ( CDSN ), and mattrin ( TMEM79 ) 72 74 .…”
Section: Food Antigen Samplingmentioning
confidence: 99%